The Legal Aspect of Fingering Mother Cap in the Making of Land & Buying Deals - Anik Setiawan (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
The research objective is to unto know and analyze application Affixing the thumbprint in making land sale and purchase deeds, unto know and analyze legal consequences of affixing a thumbprint in the making of a land sale and purchase deed, and untuk know and analyze the extent of the function Affixing the thumb print in the making of the land sale and purchase deed. This research is a qualitative research with a normative juridical approach.This research was conducted in Kendal Regency. Based on the results of research and discussion it can be seen that